Home tonight : further reflections on the parable of the prodigal son - Nouwen, Henri J. M.; Mosteller, Sue, 1933- (New York : Doubleday, 2009)
Follows the path of Nouwen's spiritual home-coming. More than three years prior to writing his great classic, The return of the prodigal son, Nouwen suffered a personal breakdown followed by a time of sealing solitude when he encoutered Rembrandt's famous painting. He reflected on and identified with the parable's characters and experienced profound and inspiring life lessons.
From loneliness to l'Arche -- The younger son -- From l'Arche to a second loneliness -- The elder son -- The hidden exile of resentment -- Homecoming to gratitude -- The primal relationship -- Touch and blessing -- Unconditional love.
Keywords: Prodigal son (Parable); Spiritual life -- Catholic Church